What can you see? In the home - Grundy, Lynn N.; Grundy, Lynn N; Grandreams Ltd. (London Grandreams Ltd., 1994)
This brightly illustrated book encourages young children to identify everyday household items through simple questions and labeled images, supporting language development and early literacy skills.
A picture book with simple questions and colourful illustrations designed to develop observational skills in young children. Cover title. No text other than questions and labels.
Ages 2-5
Keywords: Homes-Vocabulary-Picture books for children